Properties of the particle distribution in Pb–Pb collisions at sNN=5.02 TeV and sNN=2.76 TeV - Geng, Yan-Feng; Li, Bao-Chun (Frontiers in Physics, 2023)
Properties of the particle distribution in high energy heavy-ion collisions are important for understanding the particle production. In Tsallis statistics with a multisource production, we study the transverse momentum spectra of D0, D+, D*+, Ds+, J/ψ in Pb–Pb collisions at sNN = 5.02 TeV and charged particles in Pb–Pb collisions at sNN = 2.76 TeV. A good agreement can be observed between the results obtained in the model and the experimental results of ALICE and CMS collaboration. The nuclear modification factor RAA is reproduced. Properties reflected in the multiparticle system are discussed by the parameters provided in the improved model. It is found that the temperature T and the tft/τ increase with the centrality for the same particle due to the excitation degree of the multiparticle system. The non-equilibrium degree at sNN = 5.02 TeV is larger than that at sNN = 2.76 TeV. It shows that the system at the larger collision energy deviates farther from the equilibrium state.